Pengabdian Guru di Daerah Terpencil Sebagai Panggilan Iman Kristen (Studi Kasus Intrinsik) - Lebrina Lelau; Samel Sopacua (Syntax Idea)
Teacher service refers to the service by the teacher. This service is related to the teacher’s vocation which includes two aspects, namely the call to duty from the state and the call to duty from God. In thi writing the autor focuses on discussing teacher service in remote areas as a call to the Christian faith (intrinsic case study at Uspisera State Elementary School, West District). The service a teacher in a remote area is full of the various realities of local community life which are far from progress and full of various life challenges that await according to the conditions of the area. West Wetar District is located at the western tip of Southwest Maluku and has limited access to sea an land transportation. Apart from that, there is no source of fresh water on this island becauses the island is barren, so people use rainwater and water from dug wells, even thought it is salty, to meet their daily needs. Referring to the reality experienced, this research aims to raise the enthusiasm and motivation of young teachers, to serve in this place by understanding that the task of service is a task sent from God, as well as contributing to the Regional Government to conduct trining for young teachers and help provide supporting facilities for teachers. The results obtained from this research are that the view of sending that is integrated in the service of previous teachers opens up opportunities dor young teachers, namely by increasing the number of teachers nd the availability of facilities to meed living needs which continues to increase.